How Digital Communication is Reshaping Interpersonal Relationships in Urban India: A Study of Communication Trends Among Young Adults - Holkar, Raktavati (Journal of Public Representative and Society Provision, 2022)
The present research aims at understanding the pattern of self and social communication and the effects of digital interpersonal connectivity on young adults in Urban India. Online self-communication questionnaire and qualitative semi-structured interview show that although digital communication is very convenient, allowing participants to communicate often and with low levels of burden, it hinders relationship depth as well as poses psychological pressure including feelings of being overwhelmed and increased anxiety. The work also identifies a significant decrease in live physical physical contact that the participants agree impacts the richness of the bond developed with others. It points to the fact that though digital communication is an effective way of keeping in touch it should be an additional to face to face communication. Consequently, the paper establishes that digital communication should be embraced in right proportions to reap on its positives while not compromising relational quality or causing negative impacts on individuals’ psychological wellness. The findings of this research will be beneficial for members of the society, teachers and other stakeholders who seek to improve the quality of communication through technology, especially in diverse cultural settings as the ones in India.